Control attitudes and perceptions of drug use: An exploratory study - Stylianou, Stelios (My University, 2004)
Control attitudes represent opinions about the formal or informal control of a behavior by society. This study investigates control attitudes toward drug use based on data from semistructured in-depth interviews. The analysis shows that control attitudes toward drug use consist of a normative component(philosophical principles)and a perceptive component(perceptions of harm and perceptions of immorality). In particular, control attitudes are shaped by combinations of(1)libertarian principles and perceptions of harm to others,(2)paternalistic principles and perceptions of self-harm, and(3)moralistic principles and perceptions of immorality. The implications of the results in the study of normative culture are discussed.
Keywords: Offense; Penalty; Punitive attitudes